Multispecies probiotic supplementation in diet with reduced crude protein levels altered the composition and function of gut microbiome and restored microbiome-derived metabolites in growing pigs - Vasquez, Robie; Kim, Sang Hoon; Oh, Ju Kyoung; Song, Ji Hoon; Hwang, In-Chan; Kim, In Ho; Kang, Dae-Kyung (Frontiers in Microbiology, 2023)
Both crude protein (CP) and probiotics can modulate the gut microbiome of the host, thus conferring beneficial effects. However, the benefits of low CP diet supplemented with multispecies probiotics on gut microbiome and its metabolites have not been investigated in pigs. Thus, we investigated the combinatory effects of low CP diet supplemented with multispecies probiotics on gut microbiome composition, function, and microbial metabolites in growing pigs. In total, 140 6-week-old piglets (Landrace × Yorkshire × Duroc) were used in this study. The pigs were divided into four groups with a 2×2 factorial design based on their diets: normal-level protein diet (16% CP; NP), low-level protein diet (14% CP; LP), NP with multispecies probiotics (NP-P), and LP with multispecies probiotics (LP-P). After the feeding trial, the fecal samples of the pigs were analyzed. The fecal scores were improved by the probiotic supplementation, especially in LP-P group. We also observed a probiotic-mediated alteration in the gut microbiome of pigs. In addition, LP-P group showed higher species richness and diversity compared with other groups. The addition of multispecies probiotics in low CP diet also enhanced gut microbiota metabolites production, such as short-chain fatty acids (SCFAs) and polyamines. Correlation analysis revealed that Oscillospiraceae UCG-002, Eubacterium coprostanoligenes, Lachnospiraceae NK4A136 group, and Muribaculaceae were positively associated with SCFAs; and Prevotella, Eubacterium ruminantium, Catenibacterium, Alloprevotella, Prevotellaceae NK3B31 group, Roseburia, Butyrivibrio, and Dialister were positively correlated with polyamines. Supplementation with multispecies probiotics modulated the function of the gut microbiome by upregulating the pathways for protein digestion and utilization, potentially contributing to enriched metabolite production in the gut. The results of this study demonstrate that supplementation with multispecies probiotics may complement the beneficial effects of low CP levels in pig feed. These findings may help formulate sustainable feeding strategies for swine production.